Assessment of knowledge, attitude and skills towards e-learning in first year medical students - Hiwarkar, Monali; Taywade, Onjal (International Journal of Research in Medical Sciences, 2019)
Background: With digitization the e-learning modalities are being increasingly used by medical students. These often help the first MBBS students to overcome limitations of conventional teaching methods like didactic lectures. However, e-learning is not official part of medical education in India and the awareness about its use among medical students need to be evaluated. Aim and objective of the study was to assess the extent to which MBBS first year students use e-resources for learning as well as to assess knowledge, attitude, skills and habits of first MBBS students towards e-learning. Methods: A questionnaire of twenty five questions on various aspects of e-learning was administered to the first MBBS students at two medical colleges. The data generated from responses was compiled and analyzed on SPSS to get insight on various aspects of e-learning. Results: Out of 236 students surveyed 77.97% were aware about the academic websites related to first MBBS subjects. 90.68 % accepted that e-learning helped in understanding topics, 84.32% recommended conventional teaching to be supplemented with e-learning. However there was no statistically significant difference between responses from two groups i.e. female and male students (p>0.05). Conclusions: The majority of first MBBS students use e-resources for learning various topics in anatomy, physiology and biochemistry. The e-resources have made a positive impact on overall learning especially anatomy. e-learning can supplement conventional teaching in the first year of medical training.